Impact strength and mechanical properties of high strength concrete containing PET waste fiber. (1st June 2023) - Mohammed, Azad A.; Karim, Sarkawt H.
Abstract: This study presents results of tests done on workability, mechanical properties, first cracking impact and ultimate load impact of high strength concrete (HSC) contained polyethylene terephthalate (PET) waste fiber. Different PET fibers with regard the length (10 mm, 20 and 40 mm) were added to concrete by 0.50, 0.75, 1.00, 1.25 and 1.50% (by volume). Density, ultrasonic pulse velocity, compressive strength, splitting tensile strength, flexural strength, first crack impact (N1 ) and ultimate load impact (N2 ) tests were conducted on sixteen HSC mixes. Results showed a slight change in ultrasonic pulse velocity, while addition of PET fiber with 10 mm, 20 mm and 40 mm length reduced compressive strength by a maximum value of 15.74, 14.37 and 10.28% respectively compared to control concrete. Regardless to the fiber length and fraction volume, fiber content improves splitting tensile and flexural strengths by a maximum of 63.3% and 24.7% respectively. Striking results were recorded against impact strength property, in which improvement in N1 recorded up to 300% and N2 up to 833% depending on fiber length and fraction volume. It is concluded that PET waste fiber can improve important properties of HSC and it is recommended to be added to concrete by up to 1.5% by volume. Regression analysis was made to develop equations for calculating N1 and N2, and these properties were found to depend essentially on compressive strength of plain concrete and PET fiber parameters. Highlights: Workability, mechanical, first crack and ultimate load impacts of HSC containing PET fiber were investigated. There is a compressive strength reduction and splitting tensile, flexural and impact strengths enhancement due to PET fiber addition to HSC. Cut specimen taken from standard cylinder showed lower blows resistance. Equations were proposed to calculate impact strength depending on compressive strength and PET fiber parameters.